Propuesta interiorista de readecuación de las instalaciones de la piscina de “El Batán” - Andrade Espindola, Ximena Elizabeth (2016)
This Project is about a redesign of a sport center that has as an object to improve and optimize spaces to give comfort and that can develop better physical activities, which in this case focuses on the swimming practice. The building that was chosen for this project is located in the North of the city of Quito, the building has one floor, parking area, and especially a pool where activities are practiced, the main thing of this project is to highlight and rescue the spaces and to integrate the interior with the exterior and the green areas. As part of the interior architecture proposal it has been considered important to provide space for multiple activities related to sport, with recreational areas and physical activities, in addition to a space for relaxation and entertainment, so it encourages people to practice sport and also feel comfortable by good facilities and attention they would have within the building. For the development of this project I have been studied considering some aspects, natural and artificial light, materials and shapes. Thought all these studies is to develop some key areas, administrative area, wet area, social area and pool were defines.